The Relationship between Patient Safety Culture and Missed Nursing Care among nurses of Shahid Sadoughi University of Medical Sciences - Fallah, Bahare; Bolandian-Bafghi, Shahnaz; Nasiriani, Khadije; Tavangar, Hossein; Nabiazadeh- Gharghozar, Zohreh (Advances in Nursing & Midwifery, 2024)
Introduction: Cultivating a patient safety culture within an organization is essential for enhancing patient safety. This culture is closely tied to nursing practices, and any lapses in care can significantly compromise the delivery of safe nursing services. As such, missed nursing care is closely associated with the broader patient safety culture. This study aims to explore the relationship between patient safety culture and missed nursing care. Methods: This descriptive-correlational study was conducted between 2022 and 2023 with nurses at Shahid Sadoughi University of Medical Sciences. The inclusion criteria were: having a minimum of a bachelor’s degree in nursing, at least six months of experience in the department, and willingness to participate. Stratified random sampling was used for participant selection. Data were collected using a demographic questionnaire, the Kalisch and Williams Missed Nursing Care Questionnaire, and the HSOPS Questionnaire. Data analysis was performed using SPSS software (version 22), with statistical methods including descriptive statistics, t-tests, one-way ANOVA, linear regression, and Pearson correlation. Results: The study sample comprised 233 nurses, including 94 males and 139 females. The results revealed a statistically significant difference in the mean score of overall patient safety culture based on work experience (p-value < 0.001), working hours (p-value < 0.001), and work shifts (p-value < 0.001). However, no significant difference was found in the total mean score of missed nursing care across different age groups (p-value = 0.287), work experience (p-value = 0.294), and shift work (p-value = 0.059), although a significant difference was observed with weekly working hours (p-value = 0.002). These findings were further supported by univariate linear regression analysis. The Pearson correlation coefficient indicated a significant negative correlation between missed nursing care and patient safety culture. Conclusions: This research enhances our understanding of the relationship between patient safety culture and missed care. By exploring this connection, it provides empirical evidence for improving care quality and its management, while also laying the groundwork for future research in this area.